2003
DOI: 10.1212/wnl.60.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a putative protein degradation gene LITAF/SIMPLE in Charcot-Marie-Tooth disease 1C

Abstract: Mutations in LITAF may account for a significant proportion of CMT1 patients with previously unknown molecular diagnosis and may define a new mechanism of peripheral nerve perturbation leading to demyelinating neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
126
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 30 publications
9
126
0
5
Order By: Relevance
“…Interestingly, mutations in ABC1 result in Tangiers disease, which commonly presents with a peripheral demyelinating neuropathy (29). Likewise, LITAF, which is mutated in patients with demyelinating neuropathy variant CMT1C (30), was also present in this injury-associated set (Fig. 8B).…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, mutations in ABC1 result in Tangiers disease, which commonly presents with a peripheral demyelinating neuropathy (29). Likewise, LITAF, which is mutated in patients with demyelinating neuropathy variant CMT1C (30), was also present in this injury-associated set (Fig. 8B).…”
Section: Discussionmentioning
confidence: 88%
“…14 Among 3 PIG7/LITAF gene mutations detected in CMT1C patients, 2 occurred at the first nucleotide of the codon and one at the second. 8 These results indicate that the "minor" change of amino acid in PIG7/LITAF would not lead to protein dysfunction or pathogenesis of CMT1C and EMPD.…”
Section: Discussionmentioning
confidence: 83%
“…The study did not show whether the other allele of the PIG8 locus was lost or mutated or whether its mRNA or protein level was altered. Street et al 8 reported that heterozygous genomic mutations of PIG7/ LITAF were detected in CMT1C patients; however, its protein level in peripheral blood lymphocytes was not altered between patients and normal controls. They implied that mutated PIG7/ LITAF may reduce binding efficiency with protein interactors, thus leading to the degenerative changes of peripheral nerves in CMT1C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMT1C disease is caused by mutations in the lipopolysaccharide-induced tumor necrosis factor-α (LITAF) gene on chromosome 16p12-16p13.3 [1,18,19]. To date only nine pathogenic mutations in the LITAF gene have been reported [6].…”
Section: Introductionmentioning
confidence: 99%